2019
DOI: 10.2196/13687
|View full text |Cite
|
Sign up to set email alerts
|

Health Researchers’ Use of Social Media: Scoping Review

Abstract: BackgroundHealth researchers are increasingly using social media in a professional capacity, and the applications of social media for health researchers are vast. However, there is currently no published evidence synthesis of the ways in which health researchers use social media professionally, and uncertainty remains as to how best to harness its potential.ObjectiveThis scoping review aimed to explore how social media is used by health researchers professionally, as reported in the literature.MethodsThe scopi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 43 publications
0
56
0
2
Order By: Relevance
“…As described in the Methods, we categorized the sentiments expressed by the authors based on the framework proposed by Nettleton et al [ 20 ] and subsequently used by Dol et al [ 21 ]. The majority (461/543, 84.9%) of articles were celebratory in nature, followed by those that were contingent (74/543, 13.6%), and concerned (8/543, 1.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the Methods, we categorized the sentiments expressed by the authors based on the framework proposed by Nettleton et al [ 20 ] and subsequently used by Dol et al [ 21 ]. The majority (461/543, 84.9%) of articles were celebratory in nature, followed by those that were contingent (74/543, 13.6%), and concerned (8/543, 1.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for each article, we categorized the overall sentiment expressed by the authors about the usefulness of telehealth. This categorization was based on the framework developed by Nettleton et al [ 20 ] and subsequently used by Dol et al [ 21 ] in their scoping reviews of the use of internet technology and social media in medical, sociological, and popular literature. Accordingly, the sentiments were categorized as “celebratory” (ie, authors provide a positive appraisal of telehealth use during the pandemic), “contingent” (ie, authors recognize the potential positive contribution but also acknowledge its potential limitations), or “concerned” (ie, authors identify challenges and caution on the imbalance that telehealth may create in health care delivery).…”
Section: Methodsmentioning
confidence: 99%
“…The use of social media platforms to convey public opinion and attitude, has expanded rapidly over the last decade on topics related to public health, infectious disease and behavioural medicine (Dol et al, 2019;Sinnenberg et al, 2016). Social media platforms are seen as an instant method to communicate with the public (Neiger et al, 2012;Waring et al, 2019) and an opportunity to provide better understanding of the roles of healthcare professionals to better shape public perceptions (Antonoff & Stamp, 2017;Gill & Baker, 2019;Silva & Freischlag, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, social media can be used by clinicians who would benefit from the findings in dealing with patients. A recent scoping review of the literature on social media use in health research revealed that social media are increasingly used to recruit patients, collect data, and establish and maintain user engagement, especially in the name of research dissemination [ 2 ]. At the same time, in the era of the internet and web 2.0 technologies that allow content generation and sharing [ 3 ], social media have been increasingly used as a source for measuring the impact of research, as they contribute to knowledge generation, dissemination, and translation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%